A Chemically Modified Curcumin (CMC 2.24) Inhibits Nuclear Factor κB Activation and Inflammatory Bone Loss in Murine Models of LPS-Induced Experimental Periodontitis and Diabetes-Associated Natural Periodontitis - Elburki, Muna S.; Rossa, Carlos [UNESP]; Guimarães-Stabili, Morgana R. [UNESP]; Lee, Hsi-Ming; Curylofo-Zotti, Fabiana A. [UNESP]; Johnson, Francis; Golub, Lorne M. (Springer Nature, 2017)
The purpose of this study was to assess the effect of a novel chemically modified curcumin (CMC 2.24) on NF-κB and MAPK signaling and inflammatory cytokine production in two experimental models of periodontal disease in rats. Experimental model I: Periodontitis was induced by repeated injections of LPS into the gingiva (3×/week, 3 weeks); control rats received vehicle injections. CMC 2.24, or the vehicle, was administered by daily oral gavage for 4 weeks. Experimental model II: Diabetes was induced in adult male rats by streptozotocin injection; periodontal breakdown then results as a complication of uncontrolled hyperglycemia. Non-diabetic rats served as controls. CMC 2.24, or the vehicle, was administered by oral gavage daily for 3 weeks to the diabetics. Hemimaxillae and gingival tissues were harvested, and bone loss was assessed radiographically. Gingival tissues were pooled according to the experimental conditions and processed for the analysis of matrix metalloproteinases (MMPs) and bone-resorptive cytokines. Activation of p38 MAPK and NF-κB signaling pathways was assessed by western blot. Both LPS and diabetes induced an inflammatory process in the gingival tissues associated with excessive alveolar bone resorption and increased activation of p65 (NF-κB) and p38 MAPK. In both models, the administration of CMC 2.24 produced a marked reduction of inflammatory cytokines and MMPs in the gingival tissues, decreased bone loss, and decreased activation of p65 (NF-κB) and p38 MAPK. Inhibition of these cell signaling pathways by this novel tri-ketonic curcuminoid (natural curcumin is di-ketonic) may play a role in its therapeutic efficacy in locally and systemically associated periodontitis.
Keywords: bone loss; chemically modified curcumin (CMC 2.24); diabetes; lipopolysaccharide (LPS); matrix metalloproteinases (MMPs); periodontitis